AIT regulations as a case study for legal reasoning in logic programming - Nuchalee Limprasitvong; Phan, Minh Dung; Huynh, Ngoc Phien; Surapong Auwatanamongkal; DAAD - German Academic Exchange Service (Bangkok : Asian Institute of Technology, 1991)
Logic programming has been applied to a variety of examples in laws, rules and regulations of different kinds. Many researchers have suggested several ways in which the basic model of logic programming could be usefully extended for representation in the legal domain. The representation of rules and regulations of the Asian Institute of Technology in logic programming is investigated and a demonstration system for reasoning about rules and regulations is presented in this thesis. The method emphasizes both the prospects of using logic programming to build legal applications as well as its application for knowledge representation.
A thesis subm:itted .in partial fulfillinent af the requirements for the degree af Master af Science, School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 1991
Keywords: Logic programming